ANALYSIS OF DECISION MAKING PROBLEM MODELS IN SUSTAINABLE TOURISM DEVELOPMENT PLANS USING CAUSAL LOOP DIAGRAMS AND VENSIM APPLICATIONS - Husain,Muhammad Zarlis ,Herman Mawengkang,Syahril Efendi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The development of sustainable tourism is dynamic, of course it has many factors involved, so the system is complex, where each factor involved has a different purpose and management. This can lead to overlapping and even conflicts between stakeholders. Associated with the dynamic and complex challenges in the development of sustainable tourism, the ability to identify is very necessary. Therefore, this research was carried out in an effort to look more deeply into what things affect the sustainable tourism development plan and what strategies need to be optimized in the development of sustainable tourism. In need of a dynamic causal relationship analysis model of these factors using a systems approach method with a Causal Loop Diagram. (CLD) Model and generate a new multi-criteria decision analysis (MCDA) dynamic computational model that can represent conditions in terms of tourist arrivals, economic improvement and the environment that illustrates the interrelationship of interacting factors This model will look at the factors that influence the causes and effects of all the factors involved and are described in the form of a causal loop diagram that includes economic, social and environmental aspects. This model is used as consideration and decision making for sustainable tourism development planning